Balance and coordination training, but not endurance training, enhances synaptophysin and neurotrophin‐3 immunoreactivity in the lumbar spinal cord after sciatic nerve crush. Issue 4 (29th December 2015) - Bonetti, Leandro Viçosa; Ilha, Jocemar; Schneider, Ana Paula Krauthein; Barbosa, Silvia; Faccioni‐Heuser, Maria Cristina
ABSTRACT: Introduction : Numerous rehabilitation treatments have been shown to be useful for peripheral and central restoration after (PNI). Methods : After sciatic nerve crush, we investigated 4 weeks of endurance training (ET) and balance and coordination training (BCT) with sciatic function index, hind‐paw stride length, and spinal cord dorsal horn synaptophysin and neurotrophin‐3 immunoreactivity. Results : Our results demonstrated no significant differences between the non‐trained (NT), ET, and BCT groups in sciatic functional index, and in stride‐length analysis, but the ET showed higher values compared with the NT group. Synaptophysin immunoreactivity was higher in the BCT group compared with the NT group, and neurotrophin‐3 immunoreactivity in the BCT group was greater compared with the other groups. Conclusion : BCT can positively affect spinal cord plasticity after a (PNI), and these modifications are important in the rehabilitation process. Muscle Nerve 53 : 617–625, 2016